Potential effects of commonly applied drugs on neural stem cell proliferation and viability: A hypothesis-generating systematic review and meta-analysis - Mortimer, Katherine R. H.; Vernon-Browne, Hannah; Zille, Marietta; Didwischus, Nadine; Boltze, Johannes (Frontiers in Molecular Neuroscience, 2022)
Neural stem cell (NSC) transplantation is an emerging and promising approach to combat neurodegenerative diseases. While NSCs can differentiate into neural cell types, many therapeutic effects are mediated by paracrine, ‘drug-like’ mechanisms. Neurodegenerative diseases are predominantly a burden of the elderly who commonly suffer from comorbidities and thus are subject to pharmacotherapies. There is substantial knowledge about drug-drug interactions but almost nothing is known about a potential impact of pharmacotherapy on NSCs. Such knowledge is decisive for designing tailored treatment programs for individual patients. Previous studies revealed preliminary evidence that the anti-depressants fluoxetine and imipramine may affect NSC viability and proliferation. Here, we derive a hypothesis on how commonly applied drugs, statins and antihypertensives, may affect NSC viability, proliferation, and differentiation. We conducted a systematic review and meta-analysis looking at potential effects of commonly prescribed antihypertensive and antihyperlipidemic medication and NSC function. PubMed and Web of Science databases were searched according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Publications were assessed against a priori established selection criteria for relevancy. A meta-analysis was then performed on data extracted from publications eligible for full text review to estimate drug effects on NSC functions. Our systematic review identified 1017 potential studies, 60 of which were eligible for full text review. The meta-analysis was performed on 17 publications; the remainder were excluded as they met exclusion criteria or lacked sufficient data to perform a meta-analysis. The meta-analysis revealed that alpha-2 adrenoceptor agonists, an anti-hypertensive drug class (p<0.05, 95% CI= -1.54; -0.35), and various statins (p<0.05, 95% CI= -3.17; -0.0694) had an inhibiting effect on NSC proliferation. Moreover, we present preliminary evidence that L-type calcium channel blockers and statins, particularly lovastatin, may reduce NSC viability. Although the data available in the literature is limited, there are clear indications for an impact of commonly applied drugs, in particular statins, on NSC function. Considering the modes of action of the respective drugs, we reveal plausible mechanisms by which this impact may be mediated, creating a testable hypothesis, and providing insights into how future confirmative research on this topic may be conducted.